2010
DOI: 10.1007/s12098-010-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of Polycythemia in Neonates

Abstract: Polycythemia is defined as a venous hematocrit above 65%. The hematocrit in a newborn peaks at 2 h of age and decreases gradually after that. The relationship between hematocrit and viscosity is almost linear till 65% and exponential thereafter. Increased viscosity of blood is associated with symptoms of hypo-perfusion. Clinical features related to hyperviscosity may affect all organ systems. Neonates born small for gestational age (SGA), infants of diabetic mothers (IDM), and multiple births are at risk for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
3
12
0
3
Order By: Relevance
“…19 Polycythaemia in newborns may cause neurological complications, respiratory distress, myocardial dysfunction, renal vein thrombosis, hypoglycaemia, hypocalcaemia, thrombocytopenia and hyperbilirubinemia. 20 Although polycythaemia and hyperviscosity may also be encountered in healthy term infants after DCC, these effects have been reported to usually be mild and to not lead to any complications. 1,18 However, questions about DCC in infants with intra-uterine growth restriction, in LGA infants and in infants of mothers with active or passive smoking habits remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…19 Polycythaemia in newborns may cause neurological complications, respiratory distress, myocardial dysfunction, renal vein thrombosis, hypoglycaemia, hypocalcaemia, thrombocytopenia and hyperbilirubinemia. 20 Although polycythaemia and hyperviscosity may also be encountered in healthy term infants after DCC, these effects have been reported to usually be mild and to not lead to any complications. 1,18 However, questions about DCC in infants with intra-uterine growth restriction, in LGA infants and in infants of mothers with active or passive smoking habits remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies, we observed 0.6% of term singleton LGA neonates as having FM. The malnourished term AGA and LGA neonates might be under the similar metabolic and haematological risks as the term singleton SGA neonates in early postnatal, adolescent and adult life 26–30 …”
Section: Discussionmentioning
confidence: 99%
“…The malnourished term AGA and LGA neonates might be under the similar metabolic and haematological risks as the term singleton SGA neonates in early postnatal, adolescent and adult life. [26][27][28][29][30] The number of subjects in the studies investigating neonates with FM in the literature is limited to around 400-500. 15,[18][19][20] Therefore, the higher number of subjects evaluated is one of the advantages of the current study evaluated 11.741 liveborn term singleton neonates born in our hospital over the course of five and a half years.…”
Section: Discussionmentioning
confidence: 99%
“…A hiperbilirrubinémia poderá relacionar--se com a policitémia secundária ao aumento da eritropoiese, também associada a RN LIG. 35 Além dos outcomes mencionados, os critérios DGS -IADPSG não estiveram associados a redução dos partos pré-termo, partos instrumentados, complicações hipertensivas e malformações do RN.…”
Section: Resultsunclassified